Identification of 2,3-diaryl-pyrazolo[1,5-b]pyridazines as potent and selective cyclooxygenase-2 inhibitors. - Beswick, P; Bingham, S; Bountra, C; Brown, T; Browning, K; Campbell, I; Chessell, I; Clayton, N; Collins, S; Corfield, J; Guntrip, S; Haslam, C; et al. (2004)
GW406381 (8), currently undergoing clinical evaluation for the treatment of inflammatory pain is a member of a novel series of 2,3-diaryl-pyrazolo[1,5-b]pyridazine based cyclooxygenase-2 (COX-2) inhibitors, which have been shown to be highly potent and selective. Several examples of the series, in addition to possessing favourable pharmacokinetic profiles and analgesic activity in vivo, have also demonstrated relatively high brain penetration in the rat compared with the clinically available compounds, which may ultimately prove beneficial in the treatment of pain.